Evaluating the CEFR Alignment of Reading Texts in Grade 11 English Textbooks - Yani, Rindi; Musdizal, Musdizal (Universitas Pahlawan Tuanku Tambusai, 2025)
The alignment of English teaching materials with international standards was crucial in ensuring effective language learning, particularly under Indonesia’s Merdeka Curriculum. This study aimed to evaluate the conformity of reading texts in the Grade 11 English textbook Bahasa Inggris: English for Change to the Common European Framework of Reference for Languages (CEFR), an internationally recognized framework for language proficiency ranging from A1 to C2. Fifteen reading texts, which were specifically selected from the textbook’s reading comprehension sections, were analyzed using a quantitative approach. Key textual features examined included word count, average sentence length, average word length, and lexical complexity to determine each text’s CEFR level. The analysis revealed a wide range of levels, from B1 to C2, with several texts exceeding the B1–B2 target level set by the Merdeka Curriculum. This inconsistency suggested a misalignment between textbook materials and curriculum expectations, which might have affected student learning outcomes. The study underscored the importance of systematic textbook evaluation to ensure all reading materials supported the intended language proficiency goals.